Angiopatie a oko - Rencová, E (Vnitrni lekarstvi, 2010)
INTRODUCTION: Diabetic retinopathy is an important microvascular complication of diabetes as it threatens the vision. Diabetic maculopathy is the main cause of legal blindness in the adult population in western countries. The examination method involves digital fundus photography that enables comparison of the incidence, number as well as the size and the shape of pathological foci on the retina during patient visits. It, however, does not depict one important change--chronic retinal ischemia. This is identified using contrast imaging--fluorescein angiography (FAG). Administration of a contrast medium--fluorescein--into cubital vein enables depiction of non-perfused regions of the retina that form the basis for laser therapy indication as part of the prevention of proliferative diabetic retinopathy. Optical coherence tomography (OCT), during which an optical beam makes a cross-section through all 10 layers of the retina, is an important advance in the diagnostics of diabetic macular oedema. The spectral OCT (S-OCT) in particular is an analogy of a histological examination of retina but on a living tissue. RESULTS: Owing to the advances in examination techniques and treatment methods, diabetic neuropathy can now be diagnosed and treated. Early diagnosis of vascular and, consequently, tissue changes in the retina, and in its midsection in particular, is a prerequisite. Tight control of diabetes and the risk factors is sufficient to maintain good visual acuity in patients with intact inner blood-retinal barrier. In collaboration with a diabetologist, fenofibrates are used as the first line treatment when the inner blood-retinal barrier is disturbed (damaged tight junctions between endothelial cells of retinal vessels). To reduce focal macular oedema, the sources of fluid leakage into central retina are occluded using laser interventions on microaneurysms. In diffuse macular oedema, a more intensive laser technique using grid laser coagulation is applied to the central region as well as the surrounding areas of non-perfused retina. It is our view that major macular oedemas often result from an occlusion of a branch of retinal or macular venule. This is why we recommend complementing, in collaboration with a diabetologist, laser treatment of macular oedema with trombolytics. The aim of diabetic macular oedema treatment is its early elimination to avoid irreversible damage to the outer segments and later to photoreceptor cells. These changes are the main cause of the previously mentioned legal blindness in diabetic patients and are well identifiable on S-OCT. DISCUSSION: Laser therapy is the gold standard in the treatment of diabetic macular oedema as well as diabetic retinopathy. However, efficacy is lacking if diabetes and the risk factors are not tightly controlled. Instead of laser therapy to treat diabetic macular oedema with or without macular traction, some authors use a more expensive and more complicated surgery technique (pars plana vitrectomy with internal limiting membrane peeling) performed at early stages of the disease. CONCLUSION: Prevention of microangiopathy of retinal vessels through tight compensation of diabetes and the risk factors form the basis of successful treatment of diabetic retinopathy and maculopathy. At present, we are able to successfully treat developed diabetic retinopathy as well as maculaopathy, including stabilisation of visual function, subject to early diagnosis of retinal changes.
Keywords: Laser Coagulation; optická koherentní tomografie; lidé; Tomography, Optical Coherence; makulární edém; Diabetic Retinopathy; laserová koagulace; diabetická retinopatie; fluoresceinová angiografie; Fluorescein Angiography; Macular Edema; Humans